(untitled) (Praxis Educativa, 2014)
This study was framed within the problems of admission and retention of students in the first year of university. From this research, both exploratory and descriptive and explanatory, a diagnosis could be made about student characteristics, processes, skills that come into play to learn and study as well as identify the difficulties the obstacles that students confront in their learning within disciplinary fields that make up the first year curriculum of course of studies at the School of Economics, National University of Cordoba. The findings advance to meet a complex phenomenon in which there is a “meeting of cultures” (Carlino, 2011) and in which the permanence becomes the focus of concern, for which we outline a set of criteria and alternatives as suggestions that lead to review and make decisions within curricular areas and the management of the option provided.